Pkpu in Indonesia and its Comparison with the United Arab Emirates (Difc Insolvency Law) - Ariel Alexander (Eduvest - Journal of Universal Studies, 2026)
Debt restructuring is a key legal instrument to prevent liquidation and support debtor recovery. Indonesia applies the PKPU mechanism, while the DIFC uses the Insolvency Law No. 1 of 2019, reflecting different legal approaches that require comparative analysis. This research aims to analyze and compare the debt restructuring mechanism in the PKPU system in Indonesia and the Insolvency Law of DIFC, as well as assess its effectiveness in providing legal protection for debtors and creditors. This study uses normative legal methods with a statutory approach and a comparative approach. Data were obtained through literature studies and analyzed descriptively-analytically and comparatively. The results show that PKPU in Indonesia focuses on a peace mechanism through the approval of the majority of creditors with a certain time limit, while the DIFC Insolvency Law provides greater flexibility through a modern restructuring scheme with an international principles-based approach. The DIFC also provides stronger protection for creditors through transparency and more structured court oversight. In general, both systems have the same goal of saving the debtor's business and providing legal certainty for creditors. However, the restructuring mechanism in the DIFC tends to be more adaptive to international business practices, while PKPU in Indonesia still has some limitations in terms of efficiency and legal protection. Regulatory reform in Indonesia is needed to increase competitiveness and legal certainty in debt settlement.